The Physical Properties of Soil in Palm Oil Agroforetrial System (Elaeis Guineensis Jacq.) with Aloes (Aquilaria Malacensis Lamk.) and In Palm Oil Monoculture System - Feri FA Agriani; Rendika Ranuda; Wawan Wawan; Nurul Qomar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Oil palm cultivation is generally carried out in monoculture. This has an impact on decreasing soil fertility, one of which is the physical properties of the soil. One of solutions that can be done to overcome this is the cultivation of oil palm plants with an agroforestry system. The purpose of this research was to compare the physical properties of soil agroforestry on oil palm (Elaeis gueneensis Jacq.) and aloes (Aquilaria malacensis Lamk.) with oil palm in monoculture. This research was conducted in Bukit Kemuning Village, Tapung Hulu District, Kampar Regency for 4 months from November – Februari 2020. Determination research the locations for agroforestry system and monoculture system using purposive sampling method. Soil samples were taken from 4 sampling point: palm circle, leaf frond piles, harvest path and aloes circle which were repeated 6 times on each land. The observation parameters are several soil physical properties (topsoil depth, bulk density, particle density, total pore space, moisture content, water holding capacity, permeability, infiltration, and soil resistance) and soil C-organic. Data from the observations of each parameter were analyzed statistically using the t test. The results showed that the agroforestry system increased C-organic content and improved selected soil physical properties (increase topsoil depth, total pore space, moisture content, water holding capacity, permeability, infiltration and decrease bulk density, particle density and soil resistance).